Segundo Premio : Rozenwasser/Silberfaden/Caballero 1999 (1999)
Concurso Internacional de Anteproyectos <Plaza Embajada del Estado de Isarel>
Keywords: ARGENTINA; BUENOS AIRES; ROZENWASSER, PABLO; SILBERFADEN, DANIEL HORACIO; CABALLERO, GERARDO; ANTEPROYECTOS; PLAZAS; CONCURSOS; PREMIOS